Introduction. Issue 2 (9th July 2014) - Rubin, Eli
Abstract : The essays in this special issue all focus on the city of Berlin, in particular, its relationship with its margins and borders over the longue dureé . The authors—Kristin Poling, Marion Gray, Barry Jackisch, and Eli Rubin—all consider the history of Berlin over the last two centuries, with special emphasis on how Berlin expanded over this time and how it encountered the open spaces surrounding it and within it—the "green fields" ( grüne Wiesen ) referred to in the theme title. Each of them explores a different period in Berlin's history, and so together, the essays form a long dureé history of Berlin, although each of the essays in its own way explores the roots of Berlin's history in deeper time scales, from the early modern period, to the Middle Ages, and even to the very end of the last ice age, more than 10, 000 years ago.